# Solve for a (10ac)/11=-3

10ac11=-3
Multiply both sides of the equation by 1110.
1110⋅10ac11=1110⋅-3
Simplify both sides of the equation.
Simplify 1110⋅10ac11.
Cancel the common factor of 11.
Cancel the common factor.
1110⋅10ac11=1110⋅-3
Rewrite the expression.
110⋅(10ac)=1110⋅-3
110⋅(10ac)=1110⋅-3
Cancel the common factor of 10.
Factor 10 out of 10ac.
110⋅(10(ac))=1110⋅-3
Cancel the common factor.
110⋅(10(ac))=1110⋅-3
Rewrite the expression.
ac=1110⋅-3
ac=1110⋅-3
ac=1110⋅-3
Simplify 1110⋅-3.
Multiply 1110⋅-3.
Combine 1110 and -3.
ac=11⋅-310
Multiply 11 by -3.
ac=-3310
ac=-3310
Move the negative in front of the fraction.
ac=-3310
ac=-3310
ac=-3310
Divide each term by c and simplify.
Divide each term in ac=-3310 by c.
acc=-3310⋅1c
Cancel the common factor of c.
Cancel the common factor.
acc=-3310⋅1c
Divide a by 1.
a=-3310⋅1c
a=-3310⋅1c
Simplify -3310⋅1c.
Multiply 1c and 3310.
a=-33c⋅10
Move 10 to the left of c.
a=-3310c
a=-3310c
a=-3310c
Solve for a (10ac)/11=-3

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top